Gender Dynamics and Digital Literacy in Pesantren Creative Writing - Fitriyah, Atiqotul; Haryanti, Novi Diah; Fadhilla, Indah; Utama , Virdika Rizky (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
Pesantren, or Islamic boarding schools, have traditionally developed with a unique educational model. However, the advancement of digital technology has impacted education within pesantren, creating opportunities for santri (male students) and santriwati (female students) to engage in creative writing. Their writing progress is evident on the duniasantri.co platform, despite a gender disparity in the number of contributors. This study examines the contestation between santri and santriwati in creative writing using a qualitative method and digital ethnography approach. Bourdieu’s concepts of habitus, field, and capital are employed to analyze data obtained from digital footprints and in-depth interviews. The findings reveal significant contestation in digital literacy, where the symbolic capital of pesantren leaders enables santriwati to compete on an equal footing, making their writing productivity more competitive.